Cross-cultural adaptation and linguistic validation of the Hypoglycaemia Symptom Rating Scale (HypoSRQ) among Malaysian patients with diabetes mellitus - Tan, Chai Eng; Tong, Seng Fah; Aida J,; Zuhra Hamzah, (Fakulti Perubatan, UKM, 2016)
The Hypoglycaemia Symptom Rating Questionnaire (HypoSRQ) is potentially useful for local research on hypoglycaemia. However, it requires adaptation and validation in local settings. This study reports the process and results of cross-cultural adaptation and linguistic validation of HypoSRQ for Malay and English versions in our local setting. The HypoSRQ underwent forward and backward translation and adaptation with support from professional translators and a clinical psychologist. Cognitive debriefing was done among patients with Type 1 and Type 2 diabetes mellitus from varying sociodemographic backgrounds. Discussion was done together with the original developers of the HypoSRQ to decide on the best version for local use. The finalised versions were proofread and formatted with the help of Health Psychology Research. Cognitive debriefing for Malay version involved 7 patients and for the English version5 patients. Direct literal translation into Malay language was unsuitable due to technical terms which were difficult for laypersons to understand. Amendments were made based on findings from the cognitive debriefing process. Participants found the questionnaire fairly easy to understand. The HypoSRQ-My (Malay) and HypoSRQ-EMy (English) is easily understood by local participants. These tools may undergo psychometric evaluation for future use in local settings.